2018
DOI: 10.1371/journal.pone.0196081
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of quantitative miRNA panels to consolidate the diagnostic surveillance of HBV-related hepatocellular carcinoma

Abstract: BackgroundCirculating microRNAs (miRNA) are biomarkers for several neoplastic diseases, including hepatocellular carcinoma (HCC). We performed a literature search, followed by experimental screening and validation in order to establish a miRNA panel in combination with the assessment of alpha-fetoprotein (AFP) levels and to evaluate its performance in HCC diagnostics.MethodsExpression of miRNAs was quantified by quantitative PCR (qPCR) in 406 serum samples from 118 Vietnamese patients with hepatitis B (HBV)-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Table S2 included miR‐24, miR‐665, miR‐150, and miR‐296, which have been reported as upregulated in serum from individuals with HCC . However, miR‐122 and miR‐21, which were upregulated in serum from patients with HCC in many reports, were not significantly different between HCC and NC. This was presumably because very limited numbers of samples were available for NC ( n = 2) in this microarray analysis of miRNA, and we used this microarray analysis as the first screening for ETR of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S2 included miR‐24, miR‐665, miR‐150, and miR‐296, which have been reported as upregulated in serum from individuals with HCC . However, miR‐122 and miR‐21, which were upregulated in serum from patients with HCC in many reports, were not significantly different between HCC and NC. This was presumably because very limited numbers of samples were available for NC ( n = 2) in this microarray analysis of miRNA, and we used this microarray analysis as the first screening for ETR of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning plasma/serum miRNAs in HCC, several research groups have reported the potential utility of miRNAs circulating in plasma/serum in clinical applications . However, to date, few reports have described the role of circulating miRNAs in ETR, apart from reports of miRNAs in tissue samples associated with ETR …”
Section: Introductionmentioning
confidence: 99%
“…Seventeen studies were further excluded after full-text review, because they were animal studies (n = 1), not designed as diagnostic studies (n = 5), reported exosomal miR-122 expression rather than circulating miR-122 expression (n = 3), evaluated single nucleotide polymorphisms of miR-122 (n = 1), or reported diagnostic efficacies with no available data for miR-122 (n = 7). Finally, 13 studies were included [11][12][13][14][16][17][18][19][20][21][22][23][24].…”
Section: Studies Identified By Databasementioning
confidence: 99%
“…BioMed Research International [11-14, 17, 21, 23], three in Egypt [16,18,19], one in Vietnam [22], one in Italy [20], and one in Australia [24]. The characteristics of the control populations were mixed, with inclusion of healthy controls, participants with HBV or HCV infection, and patients with liver cirrhosis or dysplastic nodules.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation